Treatment outcome with a second generation combination chemotherapeutic regimen m-BACOD and with a standard regimen chop for advance diffuse non-Hodgkin's lymphoma in elderly patients - Hai, Abdul; Hossain, Sarder Mahmud; Nasiruzzaman, AK (Journal of Armed Forces Medical College, Bangladesh, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> doi:10.3329/jafmc.v4i2.1841 JAFMC Bangladesh Vol.4(2) 2008 27-32